Incompressible limit of the non-isentropic magnetohydrodynamic equations in bounded domains. Issue 3 (May 2015) - WANG, Shu; XU, Zili
Abstract The incompressible limit of the non-isentropic magnetohydrodynamic equations with zero thermal coefficient, in a two dimensional bounded domain with the Dirichlet condition for velocity and perfectly conducting boundary condition for magnetic field, is rigorously justified.